2009
DOI: 10.1155/2009/463575
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity Revaluation of Three Commercial Nitroheterocyclic Drugs: Nifurtimox, Benznidazole, and Metronidazole

Abstract: Nitroheterocyclic compounds are widely used as therapeutic agents against a variety of protozoan and bacterial infections. However, the literature on these compounds, suspected of being carcinogens, is widely controversial. In this study, cytotoxic and genotoxic potential of three drugs, Nifurtimox (NFX), Benznidazole (BNZ), and Metronidazole (MTZ) was re-evaluated by different assays. Only NFX reduces survival rate in actively proliferating cells. The compounds are more active for base-pair substitution than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 97 publications
1
23
0
4
Order By: Relevance
“…Because of their transient nature, we could not analyze the effect of these intermediates, but by analogy with the equivalent derivatives obtained from other nitroimidazoles, we can postulate that the hydroxylamine form of benznidazole could react with nucleic acids and proteins, while the nitrenium ion could conjugate with free thiols (16,45). Such interactions may account for some of this prodrug's pleiotropic effects: benznidazole is mutagenic and causes a thiol depletion (4,22). Likewise, many of these potentially trypanocidal properties could be attributed to glyoxal, the final end product of TbNTRmediated benznidazole reduction (Fig.…”
Section: Figmentioning
confidence: 99%
“…Because of their transient nature, we could not analyze the effect of these intermediates, but by analogy with the equivalent derivatives obtained from other nitroimidazoles, we can postulate that the hydroxylamine form of benznidazole could react with nucleic acids and proteins, while the nitrenium ion could conjugate with free thiols (16,45). Such interactions may account for some of this prodrug's pleiotropic effects: benznidazole is mutagenic and causes a thiol depletion (4,22). Likewise, many of these potentially trypanocidal properties could be attributed to glyoxal, the final end product of TbNTRmediated benznidazole reduction (Fig.…”
Section: Figmentioning
confidence: 99%
“…To test this we compared SOS induction in the SOS-R1 wild type versus DNA-repair mutant strains with two different mono-nitroaromatic prodrugs, the 5-nitroimidazole metronidazole and the 5-nitrofuran nitrofurazone. Nucleotide excision repair has previously been identified as the major repair pathway for nitrofurazone-induced DNA damage (Ona et al, 2009), but the mechanisms of genotoxicity and repair for metronidazole are less well understood (Buschini et al, 2009;Elizondo et al, 1996). We found that neither of these compounds had any differential effect in the ada/ogt or mutS backgrounds (not shown), whereas nitrofurazone, but not metronidazole, induced an enhanced SOSresponse in the uvrB mutant (Fig.…”
Section: Uvrb Gene Deletion Affects the Sos Response To Reduced Nitromentioning
confidence: 57%
“…5A and B) (10). Additionally, thiazole 4, unlike Bnz and Nfx (see Table S3) (6,28,29), was not mutagenic in the Ames test against the five strains recommended by the OECD, was not genotoxic in vivo at the assayed dose, and possessed a high LD 50 .…”
Section: Discussionmentioning
confidence: 96%